Rethinking Isratine - INDRA KESUMA NASUTION (Universitas Sumatera Utara, 2010)
Seizing the region became the main issue of conflict triggers. This can be seen from the Case of the Israeli-Palestinian conflict. The conflict has lasted longer and there is no acceptable solu-tion. Even a hard time to be war between the Arab-Israeli conflict in 1967. Because of concern in this conflict, Muammar Gaddafi, wrote a slim book titled 'The White Book', which offers a so-lution to the Israeli-Palestinian conflict resolution. According to Muammar Gaddafi cases this conflict can be resolved by establishing a democratic country in the region location between Is-rael and Palestine, which was named the country 'Isratine' (a combination of Israel and Pales-tine). But this idea has many problems. Israel still wants all Palestinian land. On the other hand, Palestinians who felt that the land has been taken by Israel, and Palestinians want to re-claim land they believe is their right. Feud between the two sides of this country are increa-singly frequent. Based on the study of this problem, this study concludes that Isratine is a uto-pian concept of peace.Keywords: Social conflict, International conflict, Soft diplomacy.